2016
DOI: 10.5897/ajmr2016.8211
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins production by fluorescent Pseudomonas isolated from rhizospheric soils of Malus and Pyrus

Abstract: Information on microbial production of cytokinins and their effect on plant growth are limited. Therefore, the objective of the present study was to investigate cytokinins production by Pseudomonas sp., a major component of rhizobacteria with multiform and diverse activities, which enhance plant growth by synthesizing various secondary metabolites. In the present investigations, thirty Pseudomonas isolates were isolated from the rhizosphere of Pyrus and Malus and were screened for cytokinins production (50 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…2B). Ritika et al (2012) reported that different isolates of Pseudomonas sp produced auxins like substances in the stationary phase of growth at 72 hrs of incubation period at 28°C. The homogeneity of the partially purified auxins was checked by thin layer chromatography and auxins gave the maximum Rf value of 0.81 in solvent system isopropanol: water (3:2).…”
Section: Resultsmentioning
confidence: 99%
“…2B). Ritika et al (2012) reported that different isolates of Pseudomonas sp produced auxins like substances in the stationary phase of growth at 72 hrs of incubation period at 28°C. The homogeneity of the partially purified auxins was checked by thin layer chromatography and auxins gave the maximum Rf value of 0.81 in solvent system isopropanol: water (3:2).…”
Section: Resultsmentioning
confidence: 99%
“…Продукция ЦК является относительно обычным признаком PGPR и эндофитных бактерий. PGPR могут влиять на концентрацию ЦК в растении путем синтеза ЦК или изменения гомеостаза ЦК в растении [15]. Растения Platycladus orientalis, инокулированные штаммом PGPR B. subtilis, продуцирующим ЦК, имели повышенный уровень ЦК в побегах и были более устойчивыми к засухе [16].…”
Section: продуцирование фитогормоновunclassified
“…Cytokinin (CK) is another important class of phytohormones that assists plants in growth and development and in attributing resistance to different stresses (O'Brien and Benková, 2013). Though a common trait of PGPRs, they suffice plants of CK by either synthesizing it or altering its homeostasis in plants (Dodd et al, 2010;Pallai et al, 2012;Kapoor and Kaur, 2016). The inoculation of Pseudomonas sp.…”
Section: Maintenance Of Hormonal Balancementioning
confidence: 99%